Mastering your fellowship - Klaus B. von Pressentin; Mergan Naidoo; Idongesit S. Ukpe; Tasleem Ras (South African Family Practice)
The series, ‘Mastering your Fellowship’, provides examples of the question format encountered in the written and clinical examinations, Part A of the FCFP (SA) (Fellowship of the College of Family Physicians [SA]) examination. The series is aimed at helping family medicine registrars (and their supervisors) prepare for this examination. Model answers are available online.